Effective Compression and a Minimally Invasive Rail Plate to Optimize Bone Transport in Distraction Osteogenesis - E. López-Carreño, MD; E.P. López Avendaño, MD; L. Padilla Rojas, MD; A.Y. Martínez-Castellanos, MSc; I. Arámbula Rodríguez, MD; C. García López, MD; H. Campos Huerta, MD; L. Flores Huerta, MD (JBJS Open Access)
Background:. Bone transport in distraction osteogenesis is an effective, well-known procedure. However, bone compression is an aspect of this technique for which there is no objective information. The lack of direct bone compression measurements may result in a lack of uniformity in the bone transport process, which can result in its ineffective application and may be contributing to its underutilization. This study describes the results of applying objectively measured compressions to achieve a distraction regeneration zone and docking site consolidation during bone transport in distraction osteogenesis. Methods:. This prospective study describes the results of a single cohort of 32 patients who underwent distraction osteogenesis with bone transport utilizing a combination of a minimally invasive rail plate and monolateral external fixation. The patients were categorized into 2 groups: (1) those with hypertrophic, atrophic, or infectious pseudarthrosis-nonunion (the pseudarthrosis-nonunion group), and (2) those with bone loss due to trauma or osteomyelitis (the bone loss group). The initial bone compression was measured during the latency phase, and the final compression was measured during the distraction phase. The healing index, external fixation index, healing time, consolidation time, and docking time were calculated for each patient. The Mann-Whitney U and Kruskal-Wallis tests were used for comparisons between and within groups. Results:. In this study, 28 (88%) of the patients were male. The mean patient age was 44.93 ± 16.21 years. The median values were 3.2 Nm for the initial compression and 3.4 Nm for the final compression, with no significant difference between or within groups of patients. The osseous results were excellent in 29 patients (91%), and the functional results were good or excellent in 31 patients (97%). Conclusions:. This study is the first to objectively measure compression in the bone transport process. Our findings showed that all patients who had an initial compression of ≥3.2 Nm achieved 100% consolidation of the distraction regeneration zone, and those who had a final compression of ≥2.9 Nm achieved complete docking site consolidation without complications. These 2 values thus represent effective compression and highlight the role of bone compression in bone transport. Level of Evidence:. Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.